(untitled) (Sir Salimullah Medical College Journal, 2025)
Background: Anderson-Hynes pyeloplasty( A-H pyeloplasty ) is the established treatment for hydronephrosis. The early post-operative outcomes are variable due to use of different type of trans-anastomotic or trans-renal drainage either internal or external. It is important to evaluate the transanastomotic drainage of the pelvis after removal of the stent for the effectiveness of the procedure. The frequency and timing of follow up by imaging after A-H pyeloplasty is changeable, renal ultrasonography is commonly used. The aim of the was to document the volumetric changes of renal pelvis following A-H pyeloplastyand assess the urinary drainage through new pelvi-ureteric junction. Methods: This cohort study included 15 children who underwent A-H pyeloplasty due to pellvi-ureteric junction obstruction (PUJO) .Urinary drainage was evaluated as a term of renal pelvic volume by ultrasonography post-operatively before and after diuretic use. Antero-posterior pelvic diameter (APPD), cortical thickness (CT) and pelvi-cortical ratio (P/C ratio) was also recorded. Results: Mean APPD was 30.16mm in 1st visit, 24.16 mm in 2nd visit and 18.69 mm in 3rd visit. The improvement was notable but that was not statistically significant. Measured mean CT was 5.20 mm, 6.04 mm and 8.60 mm in 1st, 2nd, and 3rd visit respectively. The mean P/C ratio was 7.64 in 1st visit, 5.02 in 2nd visit and 2.97 in 3rd visit. At 3rd visit, CT value improved and P/C ratio decreased significantly. Mean pelvic volume at baseline was 28.28 mm and after diuretics 29.03 mm on first visit that was statistically significant. Like that 2nd and 3rd visit also significant. Conclusion: Improvement of postoperative pelvic volume, APPD , CT and P/C ratio can provide objective guidance to surgeons to decide who need early follow-up, and can help for early intervention after pyeloplasty. Sir Salimullah Med Coll J 2024; 32: 65-69